ANALISIS VEGETASI GULMA PADA KEBUN SEMANGKA (Citrullus lanatus) DI DESA TIMBANGAN KECAMATAN INDERALAYA KABUPATEN OGAN ILIR PROVINSI SUMATERA SELATAN - Inka Dahlianah (Universitas PGRI Palembang, 2014)
Research on weed vegetation analysis at watermelon plantation was carried out from September to November 2014 in the village of Scales watermelon plantation Inderalaya District of Ogan Ilir South Sumatra Province. This study aims to determine the composition and structure of weed in watermelon plantations. This research is a survey directly to the field with vegetation analysis using squares method. The parameters observed see density (K), relative density (KR), Frequency (F), Relative frequencies are (FR), Importance Value Index (IVI) and the Diversity Index. Results of this study, the 9 types of weeds are Echinochloa colonum, Cynodon dactylon, Axonopus compressus, Eleusine indica, Cyperus rotundus, Asystasia coromandeliana, Cleome rutidosperma, Emilia sonchifolia and Ageratum conyzoides. The species is dominated Cyperus rotundus IVI 37.546%. Diversity of species classified as being at Hâ€™ value of 2.1.Â Key words : Analysis of vegetation, weeds, watermelon